3 A retrospective audit of mineralocorticoid receptor antagonist (mra) and device therapy following myocardial infarction (mi) complicated by left ventricular (lv) systolic dysfunction. (5th June 2017) - Mailey, Jonathan; Nicholl, Daniel
Abstract : Introduction: The EPHESUS trial demonstrated that eplerenone reduces mortality and hospitalisation from cardiac events in patients with symptomatic LV systolic dysfunction (LVSD) or diabetes following MI with LVEF 40%. The SCD-HeFT and MADIT-II trials demonstrated a reduction in mortality with the use of primary preventative ICDs in heart failure with reduced ejection fraction (HF-rEF). We conducted a retrospective audit of patients presenting with HF-rEF secondary to MI between 1/4/15 and 31/3/16. Our focus was on the initiation of MRA therapy, repeat assessment of LV function post MI and the use of device therapy if indicated. Aims: 1. Establish the proportion of eligible patients with a post MI LVEF 40% prescribed an MRA. 2. Identify whether patients with LVEF 35% are having LV imaging at 6–12 weeks and if severe LVSD persists whether device therapy is considered. Methods: Patients presenting with either NSTEMI or STEMI to The Ulster Hospital, Northern Ireland were identified using the hospitals MINAP database. Data regarding these patients was collected using electronic patient records and echo database. Each patient with an ejection fraction 40% with clinical heart failure or diabetes was considered eligible for MRA therapy provided not contraindicated by renal function or potassium. In patients with LVEF 35% we examined whether a repeat assessment of LV function with either echo or cardiac MRI was undertaken, when it was performed, and if appropriate whether ICD/CRT had been implanted. Patients were not considered eligible for a device if they had a pre-existing device, precluding co-morbidities, failed to attend echo or if they had died as an in-patient. Results: 350 patients presented to our institution with MI. 326 of these patients underwent IP assessment of LV function. 24% of the patients had LVEF 40% and 17% had LVEF 35%. 14% of patients were considered appropriate candidates for MRA therapy, but only 47% of this cohort had been prescribed an MRA. 54 patients had LVEF 35%, however only 27 were appropriate candidates for device consideration. 85% of appropriate candidates had a repeat assessment of LV function with a mean time to repeat imaging of 107 days. 17% of these patients had ongoing severe LVSD with the remainder having improved to >35%. Only 25% of those with ongoing severe LVSD had an ICD inserted, 25% died prior to review and in 50% there was no documentation why device therapy had not been considered. Conclusions: This audit demonstrated that there is scope to improve our practice in the management of post MI patients with severe LVSD. Explanations for this may include staff education and resource pressures. The appropriate prescription of MRA therapy and implantation of ICDs have a big impact on mortality in this cohort. It is therefore of the upmost importance to address any potential barriers to compliance with guidelines in order to improve the quality of care that is delivered.